Sistem Informasi Profil Sekolah di SD Negeri 4 PUU KAPAKA menggunakan Framework Codeigniter (International Forum of Researchers and Lecturers, 2025)
The development of IT has a huge impact, so all information can be obtained easily and quickly. In addition, technology can help many humans in all activities in organizations, companies, and schools. Researchers designed an information system to provide an overview or profile of an elementary school, SD Negeri 4 Puu Kapaka. The system was built using the PHP and MySql programming languages with the codeigniter framework. The school profile information system can provide information about schools, facilities, news, and also activities that have been carried out by the school. The results of this study show that this application using the Codeigniter framework can meet the needs of the system desired by the school.